2011
DOI: 10.3109/00952990.2011.643970
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Web-Based Measures Development for GHB: Expectancies, Functions, and Withdrawal

Abstract: Background Much of what is understood regarding gamma hydroxybutyrate (GHB) treatment is based on hospital case studies for overdose and withdrawal, and there are currently no measures developed specifically for GHB or its analogs (e.g., gamma butyrolactone and 1,4-butanediol) to assess drug effect expectancies, reasons for starting use, withdrawal effects, and knowledge and opinions about use. Objectives This pilot study (N = 61) was conducted to begin measures development to assess experiences, functions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Regular GHB use may cause severe dependence and serious withdrawal symptoms upon abrupt discontinuation of chronic, frequent use [39,40,46,101]. Studies on recreational users revealed a high dependence liability in frequent, heavy GHB users [36,102]. In clinical trials with human subjects GHB displayed greater abuse liability than ethanol [16,103].…”
Section: Problematic Use: Ghb Addiction 81 Addiction Liability In Hmentioning
confidence: 99%
“…Regular GHB use may cause severe dependence and serious withdrawal symptoms upon abrupt discontinuation of chronic, frequent use [39,40,46,101]. Studies on recreational users revealed a high dependence liability in frequent, heavy GHB users [36,102]. In clinical trials with human subjects GHB displayed greater abuse liability than ethanol [16,103].…”
Section: Problematic Use: Ghb Addiction 81 Addiction Liability In Hmentioning
confidence: 99%
“…On the first day of GHB/GBL detoxification, ratings will be obtained from each participant of their symptoms of GHB/GBL withdrawal using a scale widely used for alcohol withdrawal – the Clinical Institute Withdrawal Assessment for Alcohol (CIWA-Ar) which is currently used clinically by teams to monitor GHB/GBL withdrawal [ 32 – 35 ]. The CIWA-Ar may not adequately capture all neuropsychiatric symptoms/signs [ 32 , 33 ] and the Sedation Assessment Tool (SAT) will assess behavioural disturbance [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Regular GHB use may cause severe dependence and serious withdrawal symptoms upon abrupt discontinuation of chronic, frequent use [ 36 - 38 ]. Prevalence of physical dependence in recreational GHB users ranges from 4-21%, with higher rates in heavy users [ 33 , 39 - 41 ]. Upon drug discontinuation, moderate GHB users will usually experience a mild withdrawal syndrome, but withdrawal can be more severe in chronic and heavy users of GHB and can be much more serious than previously assumed [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%